Abstract: Exploring five concepts of green roofs, their ecosystem services and economic benefits. Issue (2020)Special Issues (2020) - Wallhagen, Marita; Persson, Agneta; Wahtra, Julia; Eriksson, Åsa; Ryrholm, Nils
No abstract available